Organic acids and glucose prime late-stage fungal biotrophy in maize - Matthias Kretschmer; Djihane Damoo; Sherry Sun; Christopher W. J. Lee; Croll, Daniel; Harry Brumer; James Kronstad (My University, 2022)
Many plant-associated fungi are obligate biotrophs that depend on living hosts to proliferate. However, little is known about the molecular basis of the biotrophic lifestyle, despite the impact of fungi on the environment and food security. In this work, we show that combinations of organic acids and glucose trigger phenotypes that are associated with the late stage of biotrophy for the maize pathogen Ustilago maydis . These phenotypes include the expression of a set of effectors normally observed only during biotrophic development, as well as the formation of melanin associated with sporulation in plant tumors. U. maydis and other hemibiotrophic fungi also respond to a combination of carbon sources with enhanced proliferation. Thus, the response to combinations of nutrients from the host may be a conserved feature of fungal biotrophy.